Pedagogical practice with the TEACCH methodology: Development of digital games by people with autism spectrum disorder using Scratch - Rehfeldt, Márcia Jussara Hepp (2025)
The objective of this study is to describe a pedagogical practice carried out with subjects who have ASD and who developed digital games using the Scratch platform, based on the characteristics of the TEACCH methodology. Regarding the methodology, this research is of a qualitative nature, with the participation of two subjects with ASD. For data collection, participant observation was conducted, along with the collection of materials they produced. Thematic analysis (Braun; Clarke, 2006) was used for interpreting the materials they produced. We also sought to investigate the context of the participating subjects' scenario, encouraging approaches to concepts relevant to the content taught. The main results helped to understand that efforts to combine technologies and learning methodologies aimed at subjects with ASD can contribute to the training of these students and result in significant learning (Leite, Rehfeldt; Lopes, 2019), in addition to advancement in social relationships and interactions, as well as in the process of developing autonomy. Even with challenges, considering the particularity of each participating subject, it was possible to highlight benefits provided by developing this pedagogical practice, such as creative expression, stimulation of logical thinking, improvement of social skills and engagement of participants in the digital game creation process.